Living with the Dead : twenty years on the bus with Garcia and the Grateful Dead - Scully, Rock (Little, Brown, 1996)
The Grateful Dead's manager provides an eyewitness account of the band's history, from the writing of their greatest songs and their encounters with other celebrities to their emergence as cultural icons.